Effect of Different Estrus Synchronization Protocols on Some Reproductive Traits in Nubian Goats (University of Khartoum Journal of Agricultural Sciences, 2025)
The effect of estrus synchronization protocol on theconception rates and actual kidding percentage together with litter size,birth weight, twinning rates, sex of kids and sex ratio in Nubian goatswere investigated. Eighteen Nubian goats were divided into three equalgroups. The animals in group one were treated with vaginal sponges(VSP) impregnated with 45 mg flurogestone acetate (FGA) for 18 days,followed by a single dose of 400 i.u. of pregnant mare serumgonadotrophin (PMSG) upon removal of the VSP. The second group wassubjected to a double injects of 7.5 mg prostaglandin (PGF2α), giveneleven days apart. For the third group, a vasectomies buck was suddenlyintroduced and kept with the goats for 15 days to initiate estrus. Intactbucks were used to detect heat and mate with goats in the three groups.Does treated with PGF2α and those subjected to the buck effect showedsignificantly higher pregnancy rates (66.6%) than those treated withVSP+ PMSG. (33.3%). However, the protocols of synchronization had noeffect on the kidding rates, litter size and birth weight. The type of birthcomprised both singletons and twins, but none of the three groups
Keywords: Nubian goats; estrus synchronization; reproductive traits